Multicultural Education in Middle-School: Case study in Social Studies Learning - Miftakhul, Amin; Arafat, Muhammad Yarir (Education and Talent Development Center Indonesia (ETDC Indonesia), 2024)
The purpose of this research is to define the influence of multicultural education on junior high school students' acquisition of social studies knowledge. This study employs a qualitative and descriptive research approach. This study focuses on the Middle-School 6 Sidoarjo component, namely the instructor and students. The results of the data analysis and discussion show that the classroom implementation of multicultural education in social studies is effective. Students may be well-trained to influence and make a positive impact, among other desired outcomes. Be tolerant in accepting all differences, as they are manifestations of God's grace. Do not discriminate against friends who hold different beliefs; do not impose your own beliefs on others; allow others the freedom to choose their own beliefs; refrain from interfering with others' worship; continue to interact and behave well with those who hold dissimilar beliefs in worldly matters; show respect for those who are worshiping; and refrain from hating or hurting the feelings of those with differing beliefs or opinions. We expect these manifestations of tolerance to generate constructive energy, thereby preventing conflicts or disagreements among pupils.